2010
DOI: 10.1002/ejsp.717
|View full text |Cite
|
Sign up to set email alerts
|

Why mood affects help giving, but not moral courage: Comparing two types of prosocial behaviour

Abstract: A long tradition in the help giving literature assumes that mood states determine the level of prosocial behaviour shown by individuals. Most research in this area has been conducted in the context of low cost prosocial behaviour, whereas research has been neglected in which participants were confronted with situations involving potential severe and dangerous negative consequences (i.e., high cost situations) with the help-giver risking his moral integrity and social disapproval (i.e., moral courage). To addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
81
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 59 publications
7
81
1
2
Order By: Relevance
“…This view would refine previous suggestions by Kayser et al (2010) who argue that the specific emotion of anger leads to moral courage. Indeed, anger directed toward the offender should support the moral position and encourage to stand up for one’s beliefs.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This view would refine previous suggestions by Kayser et al (2010) who argue that the specific emotion of anger leads to moral courage. Indeed, anger directed toward the offender should support the moral position and encourage to stand up for one’s beliefs.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, a behavioral conflict can result especially in prosocial individuals who tend to react more emotionally: on the one hand, they feel like withdrawing from the intimidating situation (e.g., Sekerka and Bagozzi, 2007), on the other hand, their anger fuels them into taking action (e.g., anger, Kayser et al, 2010). The net result of this fight-or-flight conflict may result in very little, while individuals with relatively high need for cognition may either experience much less of this conflict or find sufficient self-discipline or self-regulation in order to override such impulses, and act in line with their reasoning and moral standards.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, Baumert et al . () and Niesta Kayser, Greitemeyer, Fischer, and Frey () found that empathy was not reliably associated with helping in high‐cost situations, whereas the experience of anger has been identified as a significant predictor (Halmburger, Baumert, & Schmitt, ). Speaking up against uncivil and immoral behaviours is not about helping someone who is suffering.…”
Section: Discussionmentioning
confidence: 99%